110k views
2 votes
Algebra 1 question 4.

Algebra 1 question 4.-example-1
User Hirschme
by
4.8k points

2 Answers

4 votes

Greetings!

To start this problem, let's first assign a variable for the missing, consecutive odd numbers. Since they are consecutive and odd, we add two.

Proof: 3-1=2, 5-3=2

The first, consecutive, odd number:
x

The second, consecutive, odd number:
x+2

The third, consecutive, odd number:
x+4

The fourth, consecutive, odd number:
x+6

The sum of the values are equal to 3 times the sum of the first two numbers, of which this is equal to 35 less than the fourth number. Let's create an equation to simplify this:


3((x)+(x+2))=(x+6)-35

Complete the operations inside the parenthesis:


3(2x+2)=(x+6)-35

Distribute the parenthesis (utilizing the distributive property)


(((2x)(3))+((2)(3)))=(x+6)-35


(6x+6)=(x+6)-35

Simplify both sides:


6x+6=x-29

Add -6 and -x to both sides of the equation:


(6x+6)+(-6)+(-x)=(x-29)+(-6)+(-x)


5x=-35

Divide both sides of the equation by 5:


(5x)/(5)=(-35)/(5)


x=-7

If
x is equal to -7:


x+2=-5


x+4=-3


x+6=-1

The four numbers are:


\boxed{-7,-5,-3,-1}

I hope this helps!

-Benjamin

User Justin Wrobel
by
5.3k points
2 votes

1st integer - 2n+1

2nd integer - 2n+3

3rd integer - 2n+5

4th integer - 2n+7


3(2n+1+2n+3)=2n+7-35\\3(4n+4)=2n-28\\12n+12=2n-28\\10n=-40\\n=-4\\\\2n+1=-7\\2n+3=-5\\2n+5=-3\\2n+7=-1

The integers are: -7,-5,-3,-1

User Ajinkya Kulkarni
by
5.5k points